2015
DOI: 10.1016/j.ijnurstu.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

The primacy of vital signs – Acute care nurses’ and midwives’ use of physical assessment skills: A cross sectional study

Abstract: The increasing acuity of the acute care patient plausibly warrants more than vital signs assessment; however, our study confirms nurses' physical assessment core skill set is mainly comprised of vital signs. The focus on these endpoints of deterioration as dictated by early warning and rapid response systems may divert attention from and devalue comprehensive nursing assessment that could detect subtle changes in health status earlier in the patient's hospitalisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
129
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(152 citation statements)
references
References 34 publications
12
129
2
6
Order By: Relevance
“…Despite it being essential to patient safety, surveillance has been reported along with other nursing activities (i.e., ambulation, oral hygiene) that are frequently missed in hospital settings (Osborne et al., 2015). While we found mixed evidence about the relationship between nurse‐reported measures of missed care and mortality, the potential of such negative outcome calls for an in‐depth look of the issues surrounding missed care in the form of inadequate patient surveillance and its consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Despite it being essential to patient safety, surveillance has been reported along with other nursing activities (i.e., ambulation, oral hygiene) that are frequently missed in hospital settings (Osborne et al., 2015). While we found mixed evidence about the relationship between nurse‐reported measures of missed care and mortality, the potential of such negative outcome calls for an in‐depth look of the issues surrounding missed care in the form of inadequate patient surveillance and its consequences.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that nurses were routinely using vital sign-related physical assessment skills before the educational program is consistent with a previous study. [14,18] In their study on registered nurses and midwives, Osborne [18] identified a set of core skills that most nurses used all the time, including assessment of temperature, oxygen saturation, blood pressure, breathing effort, and skin, wound, and mental status.…”
Section: Frequency Of Use and Influencing Factorsmentioning
confidence: 99%
“…Recent studies on physical assessment in Austraria [16] and in Italy [17] skills have shown that about one-third of the skills learned in basic nursing education are used daily. Osborne [18] found that the core skills for acute care nurses and midwives mainly covered vital signs. The skills used also depend on nurses' areas of specialty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S4, S5, S6, and S9 are in line with this idea, indicating that observation, touch, and hearing are used as monitoring methods by assessing the patient's skin color, temperature, and respiratory pattern (depth and sounds). According to Osborne, Douglas, Reid, Jones, and Gardner (2015), although clinical deterioration requires other nursing interventions beyond the monitoring of vital signs, this was the most widely used nursing intervention. The authors believe that this finding is associated with the current focus on parameters specified by the RRSs, which could lead nurses to undervalue the performance of a more comprehensive patient assessment.…”
Section: Results and Interpretationmentioning
confidence: 99%